Characterisation of Phytophthora melonis Katsura causing collar rot of pointed gourd in Eastern India and evaluation of fungicides for its management - Lellapalli, Rithesh; Madhuri, Pattanaik; Supriya, Sahu; Dolly, Pradhan; Muhammed, Fayad A; Srinivas, Petikam; Sangeetha, Ganesan (Plant Science Today, 2026)
Pointed gourd (Trichosanthes dioica Roxb.) is an important perennial cucurbitaceous vegetable grown extensively in Eastern and Northern India. A disease caused by Phytophthora melonis infects the leaves, fruits and vines of pointed gourd, causing severe losses. Although it is known that these oomycetes cause disease in all above-ground plant parts, the mortality of plants due to extensive collar and root rot phases was observed in our study. Hence, this study aimed to characterize the pathogens associated with collar and root rot in pointed gourd, as well as its management. Two Phytophthora isolates were obtained from the collar and root rot phase, as well as eight isolates from symptomatic parts of leaves, vines and fruits. All ten isolates were subjected to morphological and molecular characterization. Basic morphological and taxonomic characteristics revealed that all ten isolates belong to Phytophthora spp., which produced non-papillate sporangia with characteristic internal proliferation. The fungi were further identified by analyzing genomic regions representing the inter-transcribed spacer (ITS) and mitochondrial cytochrome c oxidase (COX) regions. By comparing DNA sequences within the NCBI GenBank database and performing a multigene phylogenetic analysis involving the ITS and COX genes, the identity of all 10 isolates was confirmed as P. melonis. In vitro evaluation of fungicides using poisoned food and detached leaf assays demonstrated the efficacy of dimethomorph, tebuconazole, copper hydroxide and selected premixed fungicide combinations in controlling P. melonis growth. These findings highlight the potential of these fungicides for field applications in managing diseases caused by P. melonis.